"Jag söker ett värdelöst guld ett guld som gör värdelöst guldet, allt guld!": Några ingångar till den litterära värdediskursens labyrint - Mortensen, Anders (Tidskrift för litteraturvetenskap, 2014)
”I am looking for a worthless gold / a gold that makes worthless / the gold, all gold!” Some entrances to the labyrinth of the literary value discourse This article examines the modern concept of literary value. Since the late 18th century, the problem of literary value has been regarded, from the point of view of the so called double discourse of value, as a presupposed opposition between material and spiritual ”economies”. Many Romanticist and Modernist authors believe that literature – and in a broader sense art and aesthetics – constitute a value system that is analogous to, but in conflict with, and moreover has priority over, the value system of money. Through a study of Gunnar Ekelöf’s poem ”The Alchemist”, and a series of textual examples from François Villon, Johann Wolfgang von Goethe, Arthur Rimbaud, August Strindberg and Ezra Pound, the paradoxical axiology of aesthetic economy and its characteristic trope of mutually excluding values is expounded as a significant and influential ideology of modern literature. The article then discusses the scholarly use of the value discourses. What happens when researchers not only study the historical manifestations of double discourse of value, but also employ the highly contradictory concept of literary value as an analytical tool? Finally, some remarks are made regarding the benefits and shortcomings of the discourse of literary value in comparison with other vocabularies of what is meritorious in literature, concerning questions of taste, quality, or power.